O processo de escolarização em Princesa/PB: política e educação (1920-1939) - Advíncula, Charya Charlotte Bezerra (2012)
This study investigated and analyzed the process of schooling in Princesa / PB between the years 1920 and 1939. The time frame was chosen because of the economic expansion that this city suffered in the 1920s and the consequences of armed conflict of 1930, which was originated in this city and spread over almost the entire interior of Paraíba, even this being this time of great change in public education and the state of Paraíba, both in expanding the supply, and also in its structure and centralization. The town of Princesa was born prosperous in 1921 and was regarded by some scholars as one of the most important city of the state of Paraíba in the 1920s, and with prosperity the number of public schools increased, being one of the first city of Paraíba to be covered by power state with a school group, a sing of prestige of the local political leader the deputy José Pereira de Lima and a sing of modernization, by the accumulation of capital from the cultivation of cotton, a product that has created wealth and prosperity for the elite of the location. The theoretical framework chosen has helped us to understand how was the contemplation of the schools by state power to municipalities in Paraíba, in special to the princesa municipality, as well as this municipality distributed the schools financed by it. New political history. At the time, personal relationships dictate the grating of the apparatus and not the real need of the population. Although the study period coincides with the expansion of school in Paraíba, our focus has concentrated on analyzing the isolated chairs, which in that period were far more numerous than school groups, and attended, considering the object of our study, a larger portion of population, especially in villages, districts and rural areas, given that school groups were allocated in the municipalities headquarters. To make this work we used reports made by board of education of Paraíba, decrees and laws of public instruction, as well as applications and receipts for payments of teachers who taught in the municipalities of Princesa from 1920 to 1939, as well as publications of the results of public schools and provisions notices and semiannual, and annual budgets of this city, minutes from town hall, among others, we infer when we analyze the documentation concerning with the provision of public schools in the town of Princesa, that despite of having a relatively high number of public school in relation to all public schools in the state, these were insufficient for the total population in the study period, and that most of those schools were maintained by the state and they were located in the city headquarter, in the district and in some villages, and that the more distant rural areas were not covered by state schools and the city did not offer power regular schools, offing them in isolated actions with no continuity when the local power used to change its leadership.